Use of thermal imaging to collect fresh faeces for non-invasive evaluation of stress levels in the European hare (Lepus europaeus) - Skoták, Vlastimil; Cukor, Jan; Sedláček, Marek; Ševčík, Richard; Linda, Rostislav; Brynychová, Kateřina; Kostka, Matěj; Macho-Maschler, Sabine; Hušek, Jan; Palme, Rupert (Frontiers in Veterinary Science, 2025)
Assessing long-term stress in wild animal populations is extremely complicated and, in some species, practically impossible due to the complexity of sampling. Here, we tested and verified a unique non-invasive method for collecting fresh faecal samples located using thermal imaging cameras from a model species, the European hare. Subsequent analysis of faecal glucocorticoid metabolites (fGCMs) allows for the determination of stress levels without capture of individuals in hare populations. fGCM values ranged from 1.8 to 65.8 ng/g. Whilst the average value across locations in winter was 15.6 ng/g ± 9.9 SD, values in spring (April/March) were significantly higher (18.2 ng/g ± 11.2 SD; p < 0.05). These higher values coincided with the peak in European hare reproduction in spring. Significantly higher values were also confirmed in urban environments, indicating increased stress levels compared to natural environments, despite hares appearing to have adapted to the urban landscape. Higher values were also found in structurally poorer landscapes than Austrian rich agroecosystems. Having proved the usefulness of thermal imaging cameras for collecting large numbers of fresh droppings for the non-invasive evaluation of stress in wild hare sub-populations, we suggest the method could be applied to other species where capture and handling exert stress, injury or mortality.